2015
DOI: 10.1189/jlb.3a0314-132rr
|View full text |Cite
|
Sign up to set email alerts
|

Ectosomes from neutrophil-like cells down-regulate nickel-induced dendritic cell maturation and promote Th2 polarization

Abstract: DCs are the first immune cells to be exposed to allergens, including chemical sensitizers, such as nickel, a human TLR4 agonist that induces DC maturation. In ACD, DCs can interact with PMNs that are recruited and activated, leading, in particular, to ectosome release. The objective of this work was to characterize the effects of PMN-Ect on DC functions in an ACD context. We first developed a standardized protocol to produce, characterize, and quantify ectosomes by use of human PLB-985 cells, differentiated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 73 publications
2
12
0
Order By: Relevance
“…Our results suggested that the production of these cytokines was dependent on the TLR4 pathway. Moreover, we have previously shown that NiSO 4 can activate MAPK and NF-kB pathways in human DCs (Antonios et al, 2009;Turbica et al, 2015). Here we showed that IL-23/IL-12 production in NiSO 4 -activated MoDCs was also dependent on p38MAPK and NF-kB pathways at both the protein and the transcriptional levels.…”
Section: Discussionsupporting
confidence: 50%
“…Our results suggested that the production of these cytokines was dependent on the TLR4 pathway. Moreover, we have previously shown that NiSO 4 can activate MAPK and NF-kB pathways in human DCs (Antonios et al, 2009;Turbica et al, 2015). Here we showed that IL-23/IL-12 production in NiSO 4 -activated MoDCs was also dependent on p38MAPK and NF-kB pathways at both the protein and the transcriptional levels.…”
Section: Discussionsupporting
confidence: 50%
“…Several studies have led to the consensus that PMNs are able to finely regulate both innate and adaptive immune responses, engaging with T lymphocytes or antigen-presenting cells, releasing anti-inflammatory mediators or expressing regulatory receptors; this broader role in immunity also led to the definition of several functional PMN subpopulations [4,3941]. In particular, our group evidenced that isolated NETs or neutrophil-derived ectosomes were able to downregulate LPS-induced DC maturation and their capacity to induce T lymphocyte proliferation [7,42]. We also evidenced that GILZ, a potent anti-inflammatory mediator implicated in cell survival, was present in human neutrophils, promoted apoptosis via Mcl-1 downregulation, and was upregulated in patients with the acute respiratory distress syndrome in relation to severity [11,43].…”
Section: Discussionmentioning
confidence: 99%
“…Protein preparation, separation, and transfer to a polyvinylidene difluoride membrane were done, as described previously [19], before probing overnight with anti-H3cit antibody (1:100, ab5103; Abcam, Cambridge, MA, USA). Proteins were visualized on a chemiluminescence membrane reader (Chem-iDoc; Bio-Rad Laboratories) with Image Lab software (Bio-Rad Laboratories).…”
Section: Western Blot Analysismentioning
confidence: 99%